Inhibition of D4 Dopamine Receptors on Insulin Receptor Expression and Effect in Renal Proximal Tubule Cells. Issue 4 (22nd April 2016) - Zhang, Ye; Ren, Hongmei; Lu, Xi; He, Duofen; Han, Yu; Wang, Hongyong; Zeng, Chunyu; Shi, Weibin
Abstract : Background: Ion transport in the renal proximal tubule (RPT), which is increased in essential hypertension, is regulated by numerous hormones and humoral factors, including insulin and dopamine. Activation of dopamine receptor inhibits sodium reabsorption, whereas activation of insulin receptor increases sodium reabsorption in RPTs, and hyperinsulinemic animals and patients have defective renal dopaminergic system. We presume that there is an inhibition of D4 receptor on insulin receptor expression and effect, and the regulation is lost in spontaneously hypertensive rats (SHRs). Methods and Results: Insulin receptor expression was determined by immunoblotting, and Na + ‐K + ‐ATPase activity was detected in both Wistar‐Kyoto (WKY) and SHR RPT cells. Stimulation of D4 receptor with PD168077 decreased expression of insulin receptors, which was blocked in the presence of the calcium‐channel blocker, nicardipine (10 −6  mol/L per 24 hours), in cell culture medium without calcium or in the presence of inositol 1, 4, 5‐trisphosphate (IP3) receptor blocker (2‐aminoethyl diphenylborinate [2‐ADB]; 10 −6  mol/L per 24 hours), indicating that extracellular calcium entry and calcium release from the endoplasmic reticulum were involved in the signal pathway. Stimulation of the insulin receptor stimulated Na + ‐K + ‐ATPase activity, whereas pretreatment with PD168077 for 24 hours decreased the inhibitory effects of insulin receptor on Na + ‐K + ‐ATPase activity in WKY cells. However, in SHR cells, inhibition of D4 receptor on insulin receptor expression and effect were lost. Conclusions: Activation of D4 receptor inhibits insulin receptor expression in RPT cells from WKY rats. The aberrant inhibition of D4 receptor on insulin receptor expression and effect might be involved in the pathogenesis of essential hypertension.